Media “Kubinov” Berbasis Project Based Learning sebagai Strategi Pemecahan Masalah - Sringatin, Sringatin (LPPM Universitas Bina Bangsa, 2022)
The relationship between lines is one of the materials that is difficult for students to understand, because students must be able to think at a higher level, namely analyzing problems, reasoning, drawing, determining point projections on the plane, and determining auxiliary planes to find the distance from the point to the plane. Therefore, one way that can be used to help students understand the distance material on the relationship between lines is to use Kubinov. Kubinov is a teaching aid that is designed to adjust the shape of the questions on the KD relationship between point lines to the plane, especially in the shape of a cube. This study aims to describe the implementation of Kubinov media based on Project Based Learning (PJBL), as well as describe the results and impacts of using Kubinov media based on PJBL as a learning strategy in distance material on the relationship between lines. The results of using Kubinov in learning are very helpful for students to understand material concepts, improve reasoning, generate motivation and student learning outcomes. After using Kubinov increased, student learning outcomes showed an average of 87 in the distance material on the relationship between lines. Before using Kubinov, the average student was only 45